Business Ethics in the South and South East Asia - Srinivasan, Vasanthi (2011)
This article attempts to understand the state of teaching, training and research in business ethics in the South and South East Asian region. The countries surveyed are Bangladesh, Bhutan, Cambodia, India, Laos, Malaysia, Myanmar, Nepal, Pakistan, Sri Lanka, Thailand and Vietnam. The diversity across countries in the region is high in terms of economic development, political structuring and human development. The degree of privatization and globalization is varied across countries since each of them is in a different phase of transition. In an earlier survey on Business Ethics, published in 1997, India was the only country from this region that was represented. In the current survey, 12 countries from the South and South East Asia are represented. While Business Ethics in academia is widely present, Corporate Social Responsibility, Governance and Sustainability though relatively new appear to be growing rapidly. Business Ethics courses tend to focus on functional ethics, managerial ethics and implementing codes of ethical conduct. Across the 12 countries, Business Ethics is taught either as an elective or a core course in most institutions. Training emphasis across countries is varied. While training institutions in India appear to be high, the presence of multinational consultants in Thailand, Malaysia, Bangladesh and Sri Lanka is significant. The research focus across countries in the region is weak. The high convergence on the top issues in Business Ethics, across respondents in different countries, is worthy of mention.
Keywords: Teaching; Training; Research; CSR; Asia; Ethics; Business